Pengaruh Rebranding Dan Customer Service Brand Kosmetik Marcks Terhadap Loyalitas Dan Kepuasan Konsumen Di Kota Jakarta - Gen Gen Gendalasari; Anggita Pramesti; Marwan Effendy; Neni Nurisnaini (Program Vokasi dan LPPM IBI Kesatuan, 2026)
This research examines the influence of rebranding and customer service on consumer loyalty and satisfaction toward the Marcks cosmetic brand in Jakarta. As Indonesia’s beauty industry continues to grow rapidly, local brands like Marcks are challenged to remain competitive through strategic brand renewal and service improvements. Using a quantitative method with 200 respondents and data analysis via SmartPLS 4.0, the study finds that both rebranding and customer service significantly and positively affect consumer loyalty and satisfaction. These results highlight the importance of integrated marketing efforts in enhancing consumer trust and maintaining long-term relationships. The study offers strategic insights for companies aiming to sustain relevance and strengthen consumer engagement in a dynamic market.